Toward precision oncology: SERS microfluidic systems for multiplex biomarker analysis in liquid biopsy. Issue 3 (14th January 2022) - Shanmugasundaram, Karthik Balaji; Li, Junrong; Sina, Abu Ibn; Wuethrich, Alain; Trau, Matt
Abstract : Liquid biopsy-based diagnosis in precision oncology exhibits significant advantages over the traditional tissue biopsies by offering dynamic assessment of tumour heterogeneity, minimally invasive procedures for frequent sampling, and cost-effective tests. Abstract : Liquid biopsy-based diagnosis in precision oncology exhibits significant advantages over the traditional tissue biopsies by offering dynamic assessment of tumour heterogeneity, minimally invasive procedures for frequent sampling, and cost-effective tests. Implementation of liquid biopsy-based diagnosis for precision oncology could be the key to provide a confident cancer screening with tailored risk assessment, patient stratification, and real-time monitoring of cancer therapies. To achieve precision oncology with liquid biopsy, the simultaneous analysis of multiple circulating tumour biomarkers is a powerful strategy to establish an accurate signature for each individual patient. Among various developed approaches for tumour biomarker detection, microfluidic devices integrated with surface enhanced Raman scattering (SERS) are emerging as one of the powerful techniques to support precision oncology based on its potential to provide multiplexing and high sensitivity. Particularly, the microfluidic devices provide miniaturised channels for parallel reactions and SERS has the extremely narrow spectra for intrinsic multiplexing. This mini review will focus on recently reported SERS microfluidic techniques, which are capable of simultaneous detection of multiple cancer biomarkers in liquid biopsy and have the promise to be integrated into precision oncology.